How useful is thematic cartography of literature? - Döring, Jörg (Primerjalna književnost, 2013)
By discussing selected examples from literary geography, this article addresses the following questions: What is the difference between maps in fiction and maps of fiction? How mappable is fiction in general? How useful is an author's geography? What is the benefit of the distant reading enabled by literary maps as opposed to the close reading of literary texts? Should literary scholars, if they decide to map, prefer to map single texts or large groups of texts?
Keywords: literarna geografija; literarna kartografija; literature; književnost; kartiranje; zemljevidi; oddaljeno branje; toponimi